KNOWLEDGE OF REPRODUCTIVE HEALTH AMONG WOMEN AGED 15-49 AT BEN LUC DISTRICT HEALTH CENTER, LONG AN PROVINCE, 2024 (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the proportion of women aged 15-49 years with correct knowledge of reproductive health in Ben Luc district, Long An province.Research methods: A cross-sectional descriptive study was conducted among 223 women of reproductive age (15-49 years) living in Ben Luc district, Long An province, in 2024. Data were collected via face-to-face interviews with study participants.Results: The results showed that the majority of women had a moderate level of knowledge about reproductive health (76.7%). The proportion of women who knew the need for tetanus vaccination during pregnancy was 85.7%, and 87% had received counseling on postnatal care. Knowledge of contraceptive methods ranged from 82.5-89.2%. However, knowledge regarding the recognition of danger signs during pregnancy was relatively limited, at only 80.7%.Conclusions: Reproductive health knowledge among women aged 15-49 years in Ben Luc district remains at a moderate level, with notable limitations in recognizing danger signs during pregnancy. It is necessary to strengthen health education and communication activities to improve the effectiveness of reproductive health care for women in the community.
Keywords: Reproductive health, health education and communication, Long An.